2022
DOI: 10.7759/cureus.33004
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Emergency Department Visits Among End-Stage Kidney Disease Patients on Maintenance Hemodialysis in Pakistan: A Single-Center Study

Abstract: BackgroundIn this study, we aimed to determine the causes of emergency department (ED) visits by end-stage kidney disease (ESKD) patients on maintenance hemodialysis (MHD) in Karachi, Pakistan. MethodologyWe conducted a cross-sectional study that included 194 visits of ESKD patients on MHD aged ≥18 years of both genders presenting at the ED of The Kidney Centre Postgraduate Training Institute, Karachi, Pakistan between February 2021 and May 2021. The study investigated the causes behind ED visits. Frequencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, in our study, no correlation was found between hypoalbuminemia and frequency and duration of hospitalization. This can be explained as in developing countries, most common reasons 19 for hospitalization include pulmonary edema (19.1%), and catheter related infection (17%), and hypertensive urgency and emergency (14%). These complications are related to compliance to dialysis regimen and CKD medication, alongwith prolonged usage of temporary HD line access compared to perm catheters and AV fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, no correlation was found between hypoalbuminemia and frequency and duration of hospitalization. This can be explained as in developing countries, most common reasons 19 for hospitalization include pulmonary edema (19.1%), and catheter related infection (17%), and hypertensive urgency and emergency (14%). These complications are related to compliance to dialysis regimen and CKD medication, alongwith prolonged usage of temporary HD line access compared to perm catheters and AV fistulas.…”
Section: Discussionmentioning
confidence: 99%